The André Béteille omnibus : Caste, class and power : changing patterns of stratification in a Tanjore village, second edition ; The Idea of natural inequality and other essays, second edition ; Equality and universality : essays in social and political theory. - Béteille, André (Oxford University Press, 2011)
This Omnibus brings together the seminal writings of one of the country's most distinguished sociologists, Andre Beteille. It consists of three well-known books by Professor Beteille and a new Introduction written especially for this Omnibus. (I) Caste, Class and Power: Changing Patterns of Stratification in a Tanjore Village, 2/e(OUP, 1996): First published in 1965, this is a classic text in Indian sociology. A study of the changing patterns of stratification in a South Indian village, it documents the gradual transformation of the village social system hitherto structured primarily around caste distinctions. (II) The Idea of Natural Inequality and Other Essays, 2/e (OUP, 1987): The essays in this volume examine various aspects of inequality in a comparative perspective with special reference to contemporary India. They deal with the different forms and dimensions of inequality as well as with alternative conceptions of equality. (III) Equality and Universality: Essays in Social and Political Theory (OUP, 2003): This collection of essays illuminates the Indian experience in equality. It addresses issues of both social theory and social policy. It looks at the contradictions between the idea of equality and the practice of inequality, caste hierarchies, and making basic rights available to all irrespective of individual merit and need.